Analysis of the residual stress in additive manufacturing of Ti-6Al-4V. Issue 1 (1st February 2022) - Liu, Junjun; Jiang, Hao; Lei, Zhenkun; Bai, Ruixiang; Yu, Shen
Abstract: Minimizing the residual stress build-up in metal-based additive manufacturing plays a pivotal role in selecting a particular material and technique for making an industrial part. However, there are still some limitations for this application, especially the unfavourable final shape and undesired macroscopic properties of metallic parts built in additive manufacturing systems. The distortion or crack due to the residual stress of these parts leads usually to severe problems for some kinds of metal additive manufacturing technology. Therefore, it is necessary to study the distribution of residual stress in the process, which can provide an important reference for the process control of laser cladding. Taking Ti-6Al-4V (TC4) alloy as the research object, a nonlinear sequential thermal mechanical coupling model is established by combining the finite element numerical simulation and experimental deformation measurement. A least squared cost function between the Finite Element Cladding model and the experimental deformation measurement is proposed, and the finite element model updating method is constructed to retrieve the heat source parameters of TC4 Alloy in laser cladding. By comparing the numerical results with the experiment, the rationality of the inversion results of heat source parameters is verified. After that, the stress near the cladding layer is analyzed, and the influence of temperature field on the mechanical field distribution is further studied through the affects of stress distribution.